Re-examining the role of financial constraints in business cycles: Is something wrong with the credit multiplier? - Virginia Olivella; Jessica Roldán-Pe\~na (Banco de México, 2013)
Motivated by the apparent failure of the credit multiplier mechanism (CM) to deliver amplification in DSGE models, we re-examine its role in business cycles to address the question: is something wrong with the CM? Our answer is no. In coming to this answer we construct a model with reproducible capital and collateral constraints within two setups, a closed and a small open economy. Our results from the first model do not differ from the ones of previous papers. However, our main finding is that it is not the CM what fails in this type of models, but rather their ability to produce sufficient variability in prices. In particular, in this model, general equilibrium dynamics counteract the logic of price fluctuations described by theoretical models thus preventing the CM from being triggered. The second model allows us to confirm our previous claim: absent general equilibrium effects, when feeding the model with exogenous asset price dynamics, the CM is indeed an effective amplifying mechanism of shocks into the economy.
Keywords: E21; E22; E32; E44; 330; Collateral constraints; Credit multiplier; Asset prices